Measurement of skeletal density and porosity of construction materials using a new proposed vacuum pycnometer. (15th June 2022) - Park, Sungwoo; Kang, Min-Chang; Oinam, Yanchen; Amoozegar, Aziz; Pyo, Sukhoon
Highlights: A vacuum pycnometer was proposed for sekeletal density measurement. To evaluate its accuracy, it was performed on various construction materials. It can be applied to the materials in both powder form and 5-centimeter cube. The difference in density was less than 6% compared to a commercial gas pycnometer. The characteristics of other traditional methods were also discussed. Abstract: The porosity of construction materials has a direct impact on some of their properties such as sound absorption, heat transfer, and strength. Several traditional procedures have been developed to measure the porosity, however, their applications can be limited because of the low accuracy and measurement complexity among other drawbacks. This study evaluated an in-house constructed vacuum pycnometer that functions based on the ideal gas law. Its performance for determining skeletal density and porosity of a number of construction materials in the forms of powder and solid was evaluated against a commercial gas pycnometer, Archimedes' method, CT scanning, and mercury intrusion (MIP) test. Compared with the commercial gas pycnometer using He, the maximum difference was less than 4% for powder materials and less than 6% for solid materials. The test results highlight the potentials of the proposed vacuum pycnometer for measuring the skeletal density and porosity of construction materials.